Over-the-scope clip as first-line therapy for ulcers with high-risk bleeding stigmata is efficient compared to standard endoscopic therapy - Buddam, Avanija; Rao, Sirish; Koppala, Jahnavi; Rangray, Rajani; Abdussalam, Abdullah; Mukherjee, Sandeep; Chandra, Subhash (Endoscopy International Open, 2021)
Background and study aims Ulcers with high-risk stigmata have significant rebleeding rates despite standard endoscopic therapy. Data on over-the-scope clip (OTSC) for recurrent bleeding is promising but data on first line therapy is lacking. We report comparative outcomes of OTSC as first-line therapy versus standard endoscopic therapy in ulcers with high-risk stigmata.Patients and methods Consecutive adults who underwent endoscopic therapy for ulcers with high-risk stigmata between July 2019 to September 2020 were included. Patients were grouped into OTSC or standard therapy based on first-line therapy used on index endoscopy. Outcomes measured included: 1) intra-procedural hemostasis based on endoscopic documentation of adequate hemostasis; 2) 7-day rebleeding (> 2 g/dL drop in hemoglobin, hematochezia or hemorrhagic shock); 3) cost of endoscopic interventions; and 4) procedure duration measured as endoscope insertion to removal time. Cost of tools used during the index endoscopy was included. Results Sixty-eight patients were included, 47 were in standard therapy and 21 in the OTSC group. Hemostasis was achieved in 95.2 % in the OTSC group compared to 83.0 % in the standard therapy group (P = 0.256, number needed to treat [NNT]: 9). Procedure time was shorter in the OTSC group (23 vs. 16 minutes, P = 0.002). Cost of endoscopic interventions were comparable, P = 0.203. Early rebleeding was less often in OTSC group, two (9.5 %) compared to 10 (21.3 %) in standard therapy group, NNT 9. Conclusions Use of OTSCs as first-line treatment for ulcers bleed probably improves hemostasis and decreases early rebleeding. Use of OTSC as first-line therapy shortened procedure duration without increasing the cost of endoscopic interventions.